Dynamic of Serum Ferritin Level in First Trimester Pregnancy - Muniroh Muniroh; Alyya Siddiqa; Raden Partinah (Faculty of Medicine, UIN (State Islamic University) Syarif Hidayatullah Jakarta, 2020)
Background: Incidence of anemia in pregnant women was 37.1%, proportion was similar between urban vs rural areas (36.4% vs 37.8%). According to 2007 RISKESDAS, iron deficiency accounted for most common type of anemia in pregnancy. Iron deficiency anemia in pregnancy has a negative impact both on the mother and the fetus. Serum ferritin is a parameter for iron deficiency. Objective of this study was to overlook serum ferritin levels in trimester 1pregnancy.Methods: The design was retrospective cohort. Samples obtained from first trimester pregnant women who performed a pregnancy check up at Hasanah Graha Afiah Hospital Depok in the period of April 2016 - July 2017. Data were presented in percentages for categorical data. Numerical data presented in medians and ranges for abnormal data distribution; and mean and standard intersections for normal data distribution. This study involved 64 samples that met the inclusion and exclusion criteria.Results: Median serum ferritin levels in this study were still in the normal range of 40.82 (6.97 - 172.66) μg / L. Twenty one subjects (69.1%) had normal serum ferritin level (≥30 μg/L) and 47 (30.9%) had low ferritin level.Conclusions: Median serum ferritin in this study was within normal range. Low level of serum ferritin found in 21 subjects, three among them also suffered from anemia.